544 Psychosocial consequences of demonetisation in india on tea garden workers: a qualitative study in 3 districts of west bengal. (24th April 2018) - Roy, Priyanka; Grandi, Annalisa; Dasgupta, Rajib; Tripathi, Santanu K
Abstract : Introduction: The existence of a parallel cash-based economy is a major economic and political issues in India. The Government of India in a bid to curb corruption had notified ≠500 and ≠1000 as illegal tender on 8th November, 2016, and asked citizens to deposit the demonetised notes constituting 86% of total money in circulation. Commentators have indicated several hardships of common people including delayed or non-payment of wages, job loss. The tea- industry which employed 1.1 million individuals is thought to be majorly affected. However, there is no study which has assessed the psycho social consequences of demonetisation of tea garden workers (TGW's). Methods: Focus Group discussions (FGD) have been carried out with TGW's of 3 districts- Jalpaiguri, Alipurduar, and Coochbehar. In depth interviews (IDI) have been conducted with district and labour administration (4), tea garden managers (3), TGW's (6), Tea garden doctors (3), psychosocial counsellor (2), bank manger (1), worker's union (1). Semi-structured topic guide would cover- experiences of demonetisation, job satisfaction, self esteem, insecurity, absenteeism, physical discomfort, addiction. An iterative approach would be taken modifying the topic guide during the course of the study. Data would be analysed based on the general guidelines of grounded theory. Multi step data analysis includes data reduction, coding and identification of dominant themes. Ethics approval has been acquired. Results: So far interaction has identified some negative psychosocial consequences due to fear of less productivity in coming seasons, drop in prices and wages and loss of job, uncertain future and migration. However, the complete results of the study will be available by 30th August 2017. Discussion: The results of the study will provide evidence on the psycho-social consequences of TGW's in relation to the job-insecurity and economic loss, if any, due to demonetisation, may contribute in future policy formulation.